Dopamine Oxidation and Autophagy - Patricia Muñoz; Sandro Huenchuguala; Irmgard Paris; Juan Segura-Aguilar (Parkinson's Disease)
The molecular mechanisms involved in the neurodegenerative process of Parkinson's disease remain unclear. Currently, there is a general agreement that mitochondrial dysfunction, α-synuclein aggregation, oxidative stress, neuroinflammation, and impaired protein degradation are involved in the neurodegeneration of dopaminergic neurons containing neuromelanin in Parkinson's disease. Aminochrome has been proposed to play an essential role in the degeneration of dopaminergic neurons containing neuromelanin by inducing mitochondrial dysfunction, oxidative stress, the formation of neurotoxic α-synuclein protofibrils, and impaired protein degradation. Here, we discuss the relationship between the oxidation of dopamine to aminochrome, the precursor of neuromelanin, autophagy dysfunction in dopaminergic neurons containing neuromelanin, and the role of dopamine oxidation to aminochrome in autophagy dysfunction in dopaminergic neurons. Aminochrome induces the following: (i) the formation of α-synuclein protofibrils that inactivate chaperone-mediated autophagy; (ii) the formation of adducts with α- and β-tubulin, which induce the aggregation of the microtubules required for the fusion of autophagy vacuoles and lysosomes.